Gernote Kirinus: religião, política e lutas pela terra no Oeste Paranaense (1970-1980) - Chaparini, Fabiana Stahl (2018)
This research sought to analyze, from the trajectory of a social activist, the sociohistorical context of the West of Paraná, during the period from 1970 to 1980. Thus, taking as a starting point the performance of Gernote Kirinus, we sought to understand the social struggles that marked the western region of Paraná, at the time. In addition, the subject of the relationship between politics and religion was also analyzed, since Kirinus was a pastor linked to the Evangelical Church of Lutheran Confession in Brazil (IECLB). It was not the intention to elaborate a biography of the pastor, on the contrary, from his experience and performance, we sought to discuss and analyze the mobilizations carried out by the peasants of the region against the expropriation process that accompanied the construction of the Itaipu Hydroelectric Power Plant and the establishment of new standards for Brazilian agriculture, through the implementation of the modernization of agriculture project. We call attention in this case to the fact that initially Kirinus' performance had a religious sense, but as the conflicts in the region gained large proportions, he broke with the boundaries of the religious camp and began to act more directly in the political field. Circumstance that is more visible when Gernote Kirinus, in 1978 is elected state deputy by the MDB. Moment from which he started to perform outstanding and troubled, which is still little known.